2015
DOI: 10.3389/fpls.2015.00827
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines function in stress tolerance: from synthesis to regulation

Abstract: Plants are challenged by a variety of biotic or abiotic stresses, which can affect their growth and development, productivity, and geographic distribution. In order to survive adverse environmental conditions, plants have evolved various adaptive strategies, among which is the accumulation of metabolites that play protective roles. A well-established example of the metabolites that are involved in stress responses, or stress tolerance, is the low-molecular-weight aliphatic polyamines, including putrescine, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
246
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(278 citation statements)
references
References 107 publications
8
246
0
8
Order By: Relevance
“…The activities of the polyamine metabolising enzymes, are induced by stresses, resulting in enhanced stress tolerance. A number of studies have demonstrated that polyamines function in stress tolerance largely by modulating the homeostasis of reactive oxygen species (ROS) due to their direct, or indirect, roles in regulating antioxidant systems or suppressing ROS production (Liu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The activities of the polyamine metabolising enzymes, are induced by stresses, resulting in enhanced stress tolerance. A number of studies have demonstrated that polyamines function in stress tolerance largely by modulating the homeostasis of reactive oxygen species (ROS) due to their direct, or indirect, roles in regulating antioxidant systems or suppressing ROS production (Liu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines regulate plant growth, development, and responses to environmental stresses (Liu, Wang, Wu, Gong, & Moriguchi, ). Putrescine (Put), spermidine (Spd), and spermine (Spm) are three major polyamines in plants.…”
Section: Introductionmentioning
confidence: 99%
“…They were also reported to be involved in environmental stress response (Valdes-Santiago and Ruiz-Herrera, 2013; Alcazar and Tiburcio, 2014; Minocha et al, 2014; Liu et al, 2015; Pal et al, 2015), defense response (Walters, 2003; Wimalasekera et al, 2011; Zeier, 2013; Hatmi et al, 2014; Mo et al, 2015; Rossi et al, 2015) and apoptosis (Moschou and Roubelakis-Angelakis, 2014; Parhamifar et al, 2014; Cai et al, 2015). Polyamines are positively charged molecules able to interact with negatively charged molecules like RNA, DNA, proteins, polyphosphate, and phospholipids (Norris et al, 2015).…”
Section: Introductionmentioning
confidence: 99%